2013
DOI: 10.1007/s10577-013-9352-1
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased segregation of fission yeast chromosome 2 strands to daughter cells

Abstract: The base complementarity feature (Watson and Crick in Nature 171(4356): [737][738] 1953) and the rule of semi-conservative mode of DNA replication (Messelson and Stahl in Proc Natl Acad Sci U S A 44: [671][672][673][674][675][676][677][678][679][680][681][682] 1958) dictate that two identical replicas of the parental chromosome are produced during replication. In principle, the inherent strand sequence differences could generate nonequivalent daughter chromosome replicas if one of the two strands were epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…By contrast, no preferential segregation of chromosomes II and III could be detected (table 3). Consistently, a previous study examining the distribution of chromosome II also concluded that it segregates randomly between the two daughter cells [42]. Similar conclusions were drawn when stricter ranges were used, such as theoretical value ±0.025 (data not shown).…”
Section: Resultssupporting
confidence: 86%
“…By contrast, no preferential segregation of chromosomes II and III could be detected (table 3). Consistently, a previous study examining the distribution of chromosome II also concluded that it segregates randomly between the two daughter cells [42]. Similar conclusions were drawn when stricter ranges were used, such as theoretical value ±0.025 (data not shown).…”
Section: Resultssupporting
confidence: 86%
“…Thus, the hotspot recombination is proposed to occur through a pathway other than the conventional DSB repair model. In support of this hypothesis, the hotspot recombination is not reduced in the swi5 mutant, encoding a function required for general mitotic recombination in yeast (65).…”
Section: Mat1 Imprint Is a Hotspot Of Mitotic Recombination Between Hmentioning
confidence: 78%
“…A recent study (65) has reported several unusual features of the mechanism of hotspot recombination: (i) recombination occurs in the S/G2 phase of the cell; (ii) recombination occurs at an appreciable rate in about 4.0% of cell divisions; (iii) one-half of recombination events causes homozygosis, while the other half only changes linkage of markers flanking the mat1 locus; (iv) recombination occurs only between previously imprinted nonsister chromatids; and (v) recombination occurs only between chromatids that simultaneously contain DSBs/nick. These results support the armsswapping model (Fig.…”
Section: Mat1 Imprint Is a Hotspot Of Mitotic Recombination Between Hmentioning
confidence: 98%
“…More than four decades ago, an ''immortal strand'' hypothesis proposed that stem cells could retain ''immortal'' DNA strands (Cairns, 1975) to minimize the incidence of mutations, which may arise during pathological progression or aging. However, later in vivo studies using more rigorous methods and precise labeling have challenged this hypothesis (Klar and Bonaduce, 2013;Sauer et al, 2013;Schepers et al, 2011;Yadlapalli and Yamashita, 2013). On the other hand, examples of biased chromosome segregation have been reported in multiple stem cell systems, including both invertebrates and vertebrates (Rocheteau et al, 2012;Yadlapalli and Yamashita, 2013).…”
Section: Figure 7 Depolymerizing Microtubules Disrupts the Temporal Microtubule Asymmetry And Results In Randomized Sister Chromatid Segrmentioning
confidence: 99%